A radar detector with enhanced range estimation capabilities for partially homogeneous environment. Issue 9 (1st December 2014) - Aubry, Augusto; De Maio, Antonio; Foglia, Goffredo; Hao, Chengpeng; Orlando, Danilo
Abstract : In this study, the authors derive an adaptive decision scheme with enhanced range estimation capabilities for point‐like targets in partially homogeneous environments. To this end, the authors jointly exploit the oversampling of the received signal and the spillover of target energy to consecutive range samples. A suitable discrete‐time model for the received signal is introduced and the so‐called two‐step generalised likelihood ratio test is derived and assessed. The performance analysis, conducted resorting to both simulated data and real recorded datasets, is aimed at assessing the effectiveness of the proposed solution, also in comparison with the existing detectors with range estimation capabilities. The illustrative examples highlight that better detection performances and increased range estimation accuracy can be achieved exploiting oversampling at the price of an additional processing cost.